The implementation of adolescent mental health services: opportunities and challenges - Isni, Khoiriyah; Fitri, Mellyana; Jatmika, Septian Emma Dwi; De Leon, Jardene Marie Gensaya; Qomariyah, Nurul; Sulistyawati, Sulistyawati; Rachmayanti, Riris Diana (Intelektual Pustaka Media Utama, 2024)
Insufficient knowledge and information about mental health hinders the optimal use of adolescent mental health services. This qualitative case study aims to describe the utilization of adolescent mental health services (MHS) from the perspective of healthcare providers in primary health care (PHC). The primary informants were psychologists and youth care health services (YCHS) coordinators, while the triangulated informants comprised adolescents; they were selected using the purposive sampling technique. This research employs primary data collected through focus group discussions with the primary informants and in-depth interviews with the triangulated informants. The study results reported that there is no PHC providing MHS specifically designed for adolescents. Further, as low mental health literacy and stigma from parents were identified as challenges, peer support was detected to be the reinforcing factors for adolescents to access MHS. Hence, mental health literacy must be integrated into the school curriculum so that adolescent self-diagnosis does not occur.